Segment coordination to ensure the efficacy of body levers in alternative strokes - Roig, A.; Lopez, R. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Swimming is a combination of multiple small and local levers acting for the general purpose of propelling the swimmer`s body as fast as possible. The ability to link and connect each lever at the proper time will be a key to maximize its efficacy. Improving swimming coordination of arm pulls and kicks will ensure the body levers` fulcrums and allow the force induced by the swimmer to override the resistance offered by the water. Involving as many body parts as possible while swimming will enlarge the length of lever`s arm and imply a better mechanical advantage explained by Archimedes lever law. The main goal of the study is to describe how World Championship and Olympic Games elite swimmers coordinate arm pulls and kicks in alternative strokes and to justify its reason for being when seeking for efficacy of body levers while swimming. The following parameters have been used for the evaluation of swimmers coordination: number of kicks per arm pull, order and duration of kicks, start time of kicks in relation to pulling arms and overlapping between arms. Swimming distance of the race and breathing actions seem to modify arm-to-arm coordination and timing of kicks in relation to arms` underwater phase.